2020
DOI: 10.3389/fpls.2020.00657
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Effects on Biomass Carbon and Phytolith-Occluded Carbon in Grasslands Under High-Salinity Conditions

Abstract: Changes in climate and land use are causing grasslands to suffer increasingly from abiotic stresses, including soil salinization. Silicon (Si) amendment has been frequently proposed to improve plant resistance to multiple biotic and abiotic stresses and increase ecosystem productivity while controlling the biogeochemical carbon (C) cycle. However, the effects of Si on plant C distribution and accumulation in salt-suffering grasslands are still unclear. In this study, we investigated how salt ions affected majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 76 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Silicon accumulation is known to decrease the carbon content of the aboveground tissues of plants, especially grasses like rice. Liu et al [ 27 ] reported that, in their research, the C content of plants was negatively correlated with the Si content of plants, but carbon accumulation increased due to more Si being stored. Their results also suggest that Si plays an important role in regulating plant C accumulation and long-term C storage in salt-tolerant Si accumulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon accumulation is known to decrease the carbon content of the aboveground tissues of plants, especially grasses like rice. Liu et al [ 27 ] reported that, in their research, the C content of plants was negatively correlated with the Si content of plants, but carbon accumulation increased due to more Si being stored. Their results also suggest that Si plays an important role in regulating plant C accumulation and long-term C storage in salt-tolerant Si accumulators.…”
Section: Discussionmentioning
confidence: 99%
“…Digestion lasted for 2 h, then the samples were allowed to cool. We used a specific (Jones) conversion factor for the conversion of nitrogen content to protein content, which, in the case of oats, is 5.83 [ 27 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The second aliquots of the above-ground plant samples were cut into 2-mm pieces for phytolith extraction according to a wet oxidation method modified after that described by Liu et al (2020a), to obtain high amount of phytoliths by adding increased number of individual plants in the aliquot. Briefly, 2.5 g of dried plant fragments were digested in a 50 mL glass digestion tank with 25 mL concentrated HNO3 and 5 mL 30% H2O2.…”
Section: Phytolith Extraction and Characterizationmentioning
confidence: 99%
“…Furthermore, a strongly negative correlation between plant C content and phytoliths in wheat leaves under HPs suggests a defense trade-off strategy of Si substitution for C-based structural compounds in plant tissues under severe contamination scenario (Neu et al, 2017). It was suggested that high Si accumulation in plant tissues could readily biosynthesize structural components in plant cell walls with low energy cost than C-based compounds (i.e., lignin or phenolics), which might increase TTM sequestration in phytoliths (Ma et al, 2015) and lead to high biomass C accumulation, especially for Si-accumulator plants under environmental stresses (Schaller et al, 2012;Liu et al, 2020a).…”
Section: Mechanism Of Phyttm Formation As Influenced By Environmental...mentioning
confidence: 99%
“…Given that the increase in atmospheric carbon dioxide (CO 2 ) concentration strongly contributes to the dangerous effects of climate change (IPCC, 2007) much research has sought to identify practical methods to reduce atmospheric CO 2 concentration(Guo et al, 2015; Li, Song, Parr, & Wang, 2013; Parr et al, 2010; Song et al, 2011; Song et al, 2016). Recent research indicates that phytolith‐occluded carbon (PhytOC) in plants, soils, and sediments may be an important sink for CO 2 sequestered from the atmosphere (Liu, Song, et al, 2020; Parr et al, 2009; Parr et al, 2010; Parr & Sullivan, 2011; Zuo & Lu, 2011).…”
Section: Introductionmentioning
confidence: 99%